Digital literacy program to solve problematic internet use during Covid-19 pandemic for PKK families in Paremono, Mungkid, Magelang - Aftina Nurul Husna; Wulan Dewi Fatikhatus Syaidah; Urmilla Fakhrun Nisaa; Jasmine Nabila Maharani; Afifah Tiara Briliani; Dwiki Nardian Putra (Universitas Muhammadiyah Magelang, 2022)
The increase use of internet during the Covid-19 pandemic has caused various problems such as internet addiction. Children and adolescents are less able to use the internet positively and are exposed to hoax news and other negative contents. Based on the results of the FGD with the PKK (Family Welfare and Empowerment) members in Magelang Regency, it is known that the problem above occurred also in Paremono Mungkid Village, Magelang Regency. For this reason, a digital literacy program was carried out. This community service program aims to overcome problematic internet use aimed at parents and children. This socialization program consists of a series of digital literacy counseling and training activities, namely: positive internet counseling and poster making training for children, positive parenting counseling in the digital era and the dark side of cyberspace for parents, counseling on how to prevent hoaxes and internet addiction, and counseling session about age-appropriate use of smartphones and internet. As a result, based on a survey of community satisfaction with program recipients, parents and children were able to understand the material provided. Children are satisfied with the activities of using the internet and smartphones for creative and productive activities. This program produced a number of outcomes, namely counseling material modules and children's creative works.